ANTILEISHMANIAL ACTIVITY OF SOME PLANTS GROWING IN ALGERIA: JUGLANS REGIA, LAWSONIA INERMIS AND SALVIA OFFICINALIS. - Serakta, M.; Djerrou, Zouhir; Djaalab, H. Mansour; Riachi, F. Kahlouche; Hamimed, S.; Trifa, W.; Belkhiri, A.; Edikra, N.; Pacha, Y. Hamdi (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The current study was undertaken to evaluate in vitro the antileishmanial activity of three plants growing wild in Algeria : Juglans regia, Lawsonia inermis and Salvia officinalis. The hydroalcoholic extracts of these plants were tested on the growth of the promastigotes of Leishmania major. The plant extract effects were compared with three controls : CRL1 composed of 1 ml RPMI inoculated with 106 of promastigotes, CRL2 composed of 1 ml RPMI inoculated with 106 of promastigotes and 100 μl of hydroalcoholic solvent, CRL3 composed of 1 ml RPMI inoculated with 106 of promastigotes and 100 μl of Glucantim as a reference drug in the management of leishmaniasis. The results showed that both J. regia and L. inermis extracts reduced the promastigotes number significantly (P<0.01). however, S. officinalis showed a total inhibition of the Leishmania major growth.